2010
DOI: 10.1007/s11240-010-9687-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of beneficial microorganisms during in vivo acclimatization of in vitro-derived tea (Camellia sinensis) plants

Abstract: The effects of native isolates of Pseudomonas fluorescens, Azospirillum brasilense, and Trichoderma harzianum on rooting and acclimatization of in vitro-grown shoots and plantlets of tea were evaluated. In vitro bacterization of P. fluorescens failed to establish, while both T. harzianum and A. brasilense retarded shoot growth, eventually overtaking shoot cultures in in vitro rooting. Acclimatization of rooted plantlets in soil amended with bioinoculants, either individually or in various combinations, promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…A strain of Azospirillum brasilense enhanced rooting and acclimatization of Prunus cerasifera (Russo et al 2008). According to Thomas et al (2010), bacterization of explants in vitro can be unsuccessful due to lack of colonization or culture overgrowth. In many cases, better results in plantlet survival and ____________________________________________________________________________________________________________________ growth can be obtained when bioinoculants are used to amend the soil or during an in vitro rooting in the perlite, as in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…A strain of Azospirillum brasilense enhanced rooting and acclimatization of Prunus cerasifera (Russo et al 2008). According to Thomas et al (2010), bacterization of explants in vitro can be unsuccessful due to lack of colonization or culture overgrowth. In many cases, better results in plantlet survival and ____________________________________________________________________________________________________________________ growth can be obtained when bioinoculants are used to amend the soil or during an in vitro rooting in the perlite, as in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in the literature were conducted over up to 90 days (Thomas et al 2010). Despite the fact that this experiment did not observe variations between the inoculated treatments and the non-inoculated control, it is not possible to discard the hypothesis that inoculation with rhizobia can be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the positive effect of inoculation with plant-growth promoting bacteria has already been established. The acclimatization experiment of Camellia sinensis inoculated with Azospirillum showed changes in the shoot length and fresh weight after a period of 90 days (Thomas et al 2010). (Oliveira et al 2010) observed an increase in the shoot and fresh-root weight of Zingiber spectabile inoculated with Bacillus pumillus after three months.…”
Section: Discussionmentioning
confidence: 99%
“…Acclimatization is one of the important processes in plant micro propagation before plantlets/planting materials are ready to be cultivated in the field (Pospóšilová et al, 1999;Hazarika, 2003;Thomas et al, 2010). The purpose of acclimatization process is to establish plant condition from in vitro to field condition (Robinson and Sáuco, 2009).…”
Section: Copyright © 2020 Universitas Sebelas Maretmentioning
confidence: 99%